Natural fiber-reinforced light-weight cement blocks prepared from waste for sustainable development - Latda Chandeng; Thanawat Meesak; Chakrapan Tuakta; Tidarut Wisuthseriwong; Tamon Ueda; Oratai Jongprateep (Acta Polytechnica CTU Proceedings)
Low density of the light-weight cement blocks offers an advantage in terms of dead load reduction, which is advantageous in structural design-reduction of size and numbers of load-carrying structural components is possible. Production of cement blocks, however, generally requires Ordinary Portland Cement (OPC) which creates harmful environmental impacts. Utilization of waste as alternative raw materials for cement production is a route to alleviate the problem. This research aims at synthesizing eco-friendly cement-like material for production of light-weight cement blocks. The cement-like material were prepared from eggshells, cockleshells, and rice husk ash (RHA). With high content of calcium oxide and silica, eggshells and cockleshells are potential sources of calcium, whereas RHA is a good source of silicon. Additionally, a fuel-efficient solution combustion technique was employed in synthesis of the cement-like material. Phase identification analysis of the synthesized powder indicated that tri-calcium silicate (C3S), di-calcium silicate (C2S), tri-calcium aluminate (C3A),and tetra-calcium alumino ferrite (C4AF), which are main constituents of OPC, were obtained. To fabricate eco-friendly light-weight cement blocks, the synthesized cement-like material were mixed with cement, water, and additional RHA and cast into blocks. The optimal compressive strength and density of the cement blocks were in comparable range with the standard light-weight concrete defined by Thai Industrial Standards Institute (TISI) and American Concrete Institute (ACI 213,2001). With jute fiber reinforcement, enhanced compressive strength of 20% was achieved, while elimination of spalling after compression test was clearly evident, implying a more ductile failure.